Mesh Complication Rates Following Pelvic Radiation Therapy in Women With History of Synthetic Midurethral Sling Implantation. Issue 2 (February 2021) - Painter, Caitlyn E.; Geynisman-Tan, Julia; Samant, Navendu; Postlethwaite, Debbie; Ramm, Olga
Abstract : Objective: To estimate the risk of mesh complications in women with and without subsequent pelvic and abdominal radiation therapy (RT). Methods: We identified women within a large health care organization who underwent mesh-augmented surgery for pelvic floor disorders between 2008 and 2014 and subsequently received RT prior to 2018. We compared them to a randomly selected group of women who underwent similar mesh-augmented pelvic reconstructive surgery without RT in a 1:4 ratio. Mesh complications were identified through chart review corroborated with the ninth and tenth revisions of the International Classification of Diseases and Current Procedural Terminology codes for mesh complications. Mesh complications between groups were compared using survival analysis and Cox proportional hazards models. Results: We identified 36 women with RT and compared them with 144 women without RT. Indications for mesh implantation and concomitant vaginal procedures were similar between the groups. The majority of mesh implants (94.4%) were midurethral slings. Twelve mesh complications (6.7%) were identified, with similar rates in the RT (8.3%) and no-RT (6.2%) groups ( P = 0.65). The risk of mesh complications did not differ between groups when compared using the Cox proportional hazards model, controlling for age, body mass index, diabetes, menopausal status, and smoking (hazard ratio, 1.19; 95% confidence interval, 0.802–1.787). Conclusions: There was no difference in the occurrence of mesh-related complications between women with and without RT. Abdominopelvic RT may not substantially increase the risk of mesh complications following placement of a synthetic sling for stress urinary incontinence. The need for future RT may only be a minor factor in counseling patients on the risks of mesh implants for pelvic floor disorders.